PENGGUNAAN MEDIA PREZI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATA PELAJARAN PRAKARYA SUB KERAJINAN SISWA KELAS VIII.3 SMPN 1 X KOTO - BUNGA PERMATA UTARI, Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2019)
The purpose af this study was ti increase motivation ang learning outcomes in the subject of the Craft Sub Craf through the use of Prezi Media for Grade VIII.3 student of SMPN 1 X Koto.This type of research is Classroom Action Research (CAR) with the use of Prezi Media in class VIII.3 SMPN 1 X Koto. This research was conducted in twi cycles, daya collection tools in the form of teacher activity sheet, student avtivity sheet, student learning motivation questionnaires, student outcome formats. From the result of the studyshow an incrase in the student learning outcomes. In cycle I the average student learning outcomes were 72.59, in cycle II it increased to 80.19. Student learning outcomes significantly improved. From the result of study the author conclude that the use of prezi media can improve student motivation and learning outcomesKeyword : Prezi Media, Motivation, Learning outcomes